2019
DOI: 10.1038/s41598-019-46200-0
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight and grip strength in young Swedish males: a longitudinal matched sibling analysis and across all body mass index ranges

Abstract: Low birth weight is associated with a lower grip strength later in life. However, associations between birth weight among infants born at-term and factors driving associations between birth weight and grip strength are largely unknown. A cohort of 144,369 young men born at-term, including 10,791 individuals who had at least one male sibling/s, were followed until conscription where they performed a grip strength test. We used linear and non-linear regression analyses in the full cohort, and fixed-effects regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…Salonen et al 39 observed that the positive association between birth weight and LTPA observed in adults became non-significant after the inclusion of adult fat-free mass, 39 indicating that muscle mass may be a possible mediator. A low maternal pre-pregnancy BMI and a low birth weight may thus lead to lower physical activity due to lower muscle mass, 18,41,42 muscle strength, [43][44][45] muscle quality, 17 or cardiorespiratory fitness. 41,46,47 Skeletal muscle mass, BMI, physical fitness, and physical activity may mutually affect each other.…”
Section: Discussionmentioning
confidence: 99%
“…Salonen et al 39 observed that the positive association between birth weight and LTPA observed in adults became non-significant after the inclusion of adult fat-free mass, 39 indicating that muscle mass may be a possible mediator. A low maternal pre-pregnancy BMI and a low birth weight may thus lead to lower physical activity due to lower muscle mass, 18,41,42 muscle strength, [43][44][45] muscle quality, 17 or cardiorespiratory fitness. 41,46,47 Skeletal muscle mass, BMI, physical fitness, and physical activity may mutually affect each other.…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, males could only be exempt from conscriptions (requiring state approval) if they suffered from chronic disease or severe handicap [35]. Except for in sensitivity analyses, we excluded those with extreme values of weight (≤40 or ≥150 kg), height (≤150 or ≥210 cm), and/or BMI (≤15 or ≥60 kg/m 2 ) at conscription ( n = 105) in accordance with previous studies [36]. All analyses were conducted as complete-case analyses because we a priori hypothesized any missing data to be missing completely at random and potentially missing not at random in a few cases; therefore, we excluded all individuals with missing height and/or weight at conscription ( n = 76,410) and/or those with missing information on other characteristics of interest (e.g., maternal BMI and maternal smoking) ( n = 55,826) (S1 Table).…”
Section: Methodsmentioning
confidence: 99%
“…Although our aim is to examine obesity, we quantify associations between CS and all categories of BMI as compared with normal weight BMI. Weight in kilograms and height in centimetres were measured at conscription using a standardized scale and a stadiometer [36] under supervision of a nurse or physician [38]. To facilitate comparisons with previous studies, we also examined the odds of obesity (BMI ≥ 30) using all other BMI categories as reference outcome (BMI < 30).…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that individuals with extremely low (<1000 g), very low (<1500 g), and low (<2500 g) birth weights develop a physical fitness deficit during infancy until adulthood (Burns et al, 2009; Danks et al, 2013; Morrison et al, 2020; Rogers et al, 2005). Despite some inconsistency (Orterga et al, 2009; Salonen et al, 2011), poor physical fitness could be due to deficits in cardiorespiratory endurance and muscle strength (Ahlqvist et al, 2019; Clemm et al, 2012; Dodds et al, 2012; Ferreira et al, 2017; Inskip et al, 2007; Kensara et al, 2005; Moura‐dos‐Santos et al, 2013; Nobre et al, 2020). Therefore, this study aimed to evaluate whether birth weight acts as a prenatal determinant of physical fitness parameters and to determine the role of environmental or biological variables on this effect.…”
Section: Introductionmentioning
confidence: 99%